The need for the nexus approach - Salam, P.A.; Pandey, Vishnu Prasad; Shrestha, S.; Anal, A.K. (2017)
The water, energy, and food resources share a lot in common; they have strong interdependencies and are inadvertently affected by action in any one of them. Therefore, the nexus approach (integrated policies related to water, energy, and food) is required in the face of growing concerns over the future availability and sustainability of these resources. The nexus approach can help achieve at least some of the "Sustainable Development Goals (SDGs)" (e.g., SDG 2, 6, 7, 12, 13, 15). This chapter discusses trends in availability and consumption of the three key resources (i.e., water, energy, and food) and interactions between them, and finally provides some reasons why the nexus approach can help achieve social and economic development goals.